Investigation of Surface Leakage Currents of High Voltage Insulators Under Different Pollution Conditions at Power Frequency AC Voltage - Külekçioğlu, Abdülcelil; Çetin, Muhammed Sefa; Gülan, Harun; Özdemir, Mahmut Temel; Gençoğlu, Muhsin Tunay; Cebeci, Mehmet (Springer Science and Business Media Deutschland GmbH, 2026)
In this paper, the electrical behavior of high voltage insulators under different pollution conditions has been investigated experimentally at power frequency (50 Hz) alternating voltage. The main objective of the study is to reveal the effect of pollution layers on the surface leakage currents and flashover voltages of insulators. For this purpose, a climatic chamber with controllable temperature and humidity conditions, together with a 200 kV high voltage test system, was employed. Three types of insulators (standard porcelain, fog-type porcelain, and silicone composite) were tested, and artificial pollution layers of varying densities were applied to their surfaces in accordance with standard procedures. During the experiments, the surface leakage currents were recorded, and flashover voltages were determined by gradually increasing the applied voltage. The obtained data enable comparative analyses for different pollution levels and insulator types. The originality of this study lies in providing a comprehensive dataset through numerous experiments under controlled laboratory conditions, thereby addressing gaps in the existing literature. This dataset establishes a solid foundation for the modeling of insulators electrical behavior and for the development of new approaches in future research. © The Author(s), under exclusive license to Springer Nature Switzerland AG 2026.
19th International Conference on Interdisciplinarity in Engineering, INTER-ENG 2025 -- 2 October 2025 through 3 October 2025 -- Târgu Mures -- 351369
Keywords: Insulator; Leakage Current; Pollution